2022
DOI: 10.3390/bioengineering9110664
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Control with Artificial Neural Networks for Automated Insulin Delivery Systems

Abstract: Type 1 diabetes mellitus is a disease that affects millions of people around the world. Recent progress in embedded devices has allowed the development of artificial pancreas that can pump insulin subcutaneously to automatically regulate blood glucose levels in diabetic patients. In this work, a Lyapunov-based intelligent controller using artificial neural networks is proposed for application in automated insulin delivery systems. The adoption of an adaptive radial basis function network within the control sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…It was previously believed that type 1 diabetes generally occurs in childhood or adolescence 53 , but current research has found that type 1 diabetes can occur and develop throughout the entire life cycle, even in individuals over 80 years old 54 , 55 . The discovery of insulin in 1922 transformed type 1 diabetes into a treatable disease 56 , and with the intensive research of individualized treatment, clinical treatment has made great progress, including the design of insulin analogs 57 , smart insulin pumps 58 , continuous glucose sensors, and closed‐loop insulin delivery systems 59 . These advancements greatly improved blood sugar control in type 1 diabetes, reducing the frequency of diabetes‐related complications and greatly improving the long‐term outcomes of people with type 1 diabetes 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…It was previously believed that type 1 diabetes generally occurs in childhood or adolescence 53 , but current research has found that type 1 diabetes can occur and develop throughout the entire life cycle, even in individuals over 80 years old 54 , 55 . The discovery of insulin in 1922 transformed type 1 diabetes into a treatable disease 56 , and with the intensive research of individualized treatment, clinical treatment has made great progress, including the design of insulin analogs 57 , smart insulin pumps 58 , continuous glucose sensors, and closed‐loop insulin delivery systems 59 . These advancements greatly improved blood sugar control in type 1 diabetes, reducing the frequency of diabetes‐related complications and greatly improving the long‐term outcomes of people with type 1 diabetes 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…2) Sample size: In this work, sample size is chosen based on the patients whose blood glucose levels were improved. Many studies have chosen sample sizes of 13,20,25,56 [6,10,[16][17][18] to predict insulin dosage. Therefore, glucose values at the time of bolus infusion, meal time, and amount of insulin dosage given are focused on a total sample size of 60 patients.…”
Section: A Data Collection and Cohortmentioning
confidence: 99%
“…In addition, the authors in [10,11] exploited the type-2 fuzzy controller for tracking and stabilizing the blood glucose level in T1D patients. On the other hand, a radial basis function neural network was utilized in [12] as an intelligent controller for an automated insulin delivery system for a virtual patient model to monitor and control the blood glucose level within days. In another work, the authors in [13] illustrated the estimation of the T1D patient model based on a UVA/Padova metabolic simulator and designed control algorithms using an intelligent predictive control model with linear and nonlinear controllers to regulate the blood glucose level for the linear thirdorder patient model.…”
Section: Introductionmentioning
confidence: 99%